Ace school

with brainly

  • Get help from millions of students
  • Learn from experts with step-by-step explanations
  • Level-up by helping others

A community for students.

Find the product of (x + 7)(x − 7). A) x^2 − 14x + 49 B) x^2 − 49 C) x^2 + 14x + 49 D) x^2 + 49

Mathematics
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

what do you think?
x^2-49
@bahupepe explain ur answer plz

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

exactly !
The product for A. is 1) x^2 - 14x + 49 = (x-7) (x-7) = (x-7)^2
For B. its X^2-49=0 Simple and best practice solution for X^2-49=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework. If it's not what You are looking for type in the equation solver your own equation and let us solve it. Equation: Solution for X^2-49=0 equation: Simplifying X2 + -49 = 0 Reorder the terms: -49 + X2 = 0 Solving -49 + X2 = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '49' to each side of the equation. -49 + 49 + X2 = 0 + 49 Combine like terms: -49 + 49 = 0 0 + X2 = 0 + 49 X2 = 0 + 49 Combine like terms: 0 + 49 = 49 X2 = 49 Simplifying X2 = 49 Take the square root of each side: X = {-7, 7}
7x7=49 x.x=x^2 (+)(-)= - (x+7)(x-7) x.x-7x+7x-(7)(7) x^2-49

Not the answer you are looking for?

Search for more explanations.

Ask your own question